Resurfaced ZIKV EDIII nanoparticle immunogens elicit neutralizing and protective responses in vivo. Issue 5 (19th May 2022) - Georgiev, George I.; Malonis, Ryan J.; Wirchnianski, Ariel S.; Wessel, Alex W.; Jung, Helen S.; Cahill, Sean M.; Nyakatura, Elisabeth K.; Vergnolle, Olivia; Dowd, Kimberly A.; Cowburn, David; Pierson, Theodore C.; Diamond, Michael S.; et al.
Summary: Zika virus (ZIKV) is a flavivirus that can cause severe disease, but there are no approved treatments or vaccines. A complication for flavivirus vaccine development is the potential of immunogens to enhance infection via antibody-dependent enhancement (ADE), a process mediated by poorly neutralizing and cross-reactive antibodies. Thus, there is a great need to develop immunogens that minimize the potential to elicit enhancing antibodies. Here we utilized structure-based protein engineering to develop "resurfaced" (rs) ZIKV immunogens based on E glycoprotein domain III (ZDIIIs), in which epitopes bound by variably neutralizing antibodies were masked by combinatorial mutagenesis. We identified one resurfaced ZDIII immunogen (rsZDIII-2.39) that elicited a protective but immune-focused response. Compared to wild type ZDIII, immunization with resurfaced rsZDIII-2.39 protein nanoparticles produced fewer numbers of ZIKV EDIII antigen-reactive B cells and elicited serum that had a lower magnitude of induced ADE against dengue virus serotype 1 (DENV1) Our findings enhance our understanding of the structural and functional determinants of antibody protection against ZIKV. Graphical abstract: Highlights: Resurfacing of antigens by mutagenesis can selectively change antibody reactivity Display of flavivirus EDIIIs as nanoparticle immunogens enhances immune response Resurfaced immunogen (rsZDIII-2.39) elicits protective, immune-focused responses rsZDIII-2.39 produces fewer EDIII-reactive B cells and a lower degree of serum ADE Abstract : Flavivirus vaccine development is complicated by the risk of antibody-dependent enhancement (ADE), which is mediated by non-neutralizing antibodies. Georgiev et al. use structure-guided phage display to mask epitopes in the ZIKV EDIII subunit that are targeted by non-neutralizing antibodies. The resurfaced rsZDIII immunogens elicit protective but immune-focused responses in mice.